Advancements in distributed computing and Internet technologies trends and issues - Pathan, Al-Sakib Khan; Pathan, Mukaddim; Lee, Hae Young (Premier reference source, 2012)
"This book compiles recent research trends and practical issues in the fields of distributed computing and Internet technologies, providing advancements on emerging technologies that aim to support the effective design and implementation of service-oriented networks, future Internet environments and building management frameworks" - Provided by publisher